Socio-hydrological aspects of floods in commercial areas in two Brazilian basins - Fialho, Hailton César Pimentel (2021)
The frequency of flood events has increased during the last decades in Brazil. Yet, there is a lack of studies investigating citizen adaptation measures. Therefore, we studied adaptation measures used by shopkeepers to protect themselves and their businesses against floods in two different basins to verify what drives the changes in protection. Both study areas are characterized as commercial areas with major flood problem. First, the Gregorio basin located in the city of São Carlos, south-eastern Brazil with an average annual total rain of 1,361.6 mm, and the second is the Tamandaré basin located in the city of Belém, north of Brazil, with average annual rainfall of 4,000 mm the Köppen climate classification system is Cwa and Af respectively. In Gregorio basin we conducted in person interviews with twenty-three (23) merchants to collect information about a flood occurred in January 12th, 2020, characterized by a return period of 103 years. Comparing our findings with previous work in the area, we found that people increased the flood gates\' height more than 4-fold between 2015 to 2020. In Tamandaré basin we applied a questionnaire with forty-three (43) merchants to collect their viewpoints about the agents that cause the floods and what are the main implications of floods to their businesses. According to the merchants, the high tide is the main cause of flooding in the area, causing socioeconomic losses of up to 50% of their monthly income. Comparing the two basins, Gregorio suffers from floods caused by intense precipitation, the impermeabilization of the basin, and a high inclination of the land. The merchants then respond by improving their individual protection, by raising their floodgates, to prevent major damages. The Tamandaré basin, on the other hand, suffers from flooding from high tides, allowing the water to enter the drainage system, coupled with high precipitation rates which is very frequent in March and April. The merchants protect their merchandise from water but in general they don\'t use any structural protection to deal with the flood. The similarities stem from the fact that in neither of the basins the shopkeepers intend to move to a place with less risk because the areas are traditional commercial places since the foundation of the cities.